The Logos of Theism according to Zubiri - Solari, Enzo (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Secondary Literature states that the logos, in the philosophy of Zubiri, does not play any religious role independent from the reason; the Theist interpretation of the power of the real thing would be a rational subject. The religious attitudes as well as the agnostics and atheists, would only arise from the reason. It can be argued, on the contrary, that the logos affirms the religation religiously or irreligiously. The field of the reality is necessarily a means to orient in some sense the original religation. The religionis sustained in the ideas of God, and the religious judgment consists therefore of the affirmation of theists ideas. In any case, the language about the divinity (possible fundament of the power of the reality or the reality absolutely absolute) is unstable, analogical and paradoxical, it is a linguistic use minimally representative and maximally directional.
Keywords: logos; theism; reality; field; religation; religion; God; ideas; judgments; religious language